2018
DOI: 10.1115/1.4039835
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Wide-Range Centrifugal Compressor Stage for Supercritical CO2 Power Cycles

Abstract: Supercritical carbon dioxide (sCO2) power cycles require high compressor efficiency at both the design point and over a wide operating range. Increasing the compressor efficiency and range helps maximize the power output of the cycle and allows operation over a broader range of transient and part-load operating conditions. For sCO2 cycles operating with compressor inlets near the critical point, large variations in fluid properties are possible with small changes in temperature or pressure. This leads to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 20 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Five important elements to effectively avoid the surge as used in Anti-Surge Control (ASC) design are explained here [ 12 ]. .…”
Section: Surge Prevention Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Five important elements to effectively avoid the surge as used in Anti-Surge Control (ASC) design are explained here [ 12 ]. .…”
Section: Surge Prevention Methodologymentioning
confidence: 99%
“…As the technology of microprocessors arrived, the intensity of the arithmetic calculations increased, the modeling was based on polynomials for the surge limit, and unbalanced control systems were introduced. Surge control of the modern area focuses on maximizing the compressor operating zone [ [12] , [13] , [14] , [15] , [16] ]. The latest techniques of the ASC system can be reviewed in Refs.…”
Section: Surge Prevention Methodologymentioning
confidence: 99%
“…Casing treatment is a common mean of extending compressor operating range, and study of casing treatment at inlet region of impeller has still been a research hot spot in recent years [9][10][11][12][13][14]. Latest research shows that rotating stall phenomenon is observed in flow channel of vane diffuser of centrifugal compressor [15,16], so studies of casing treatment in diffuser area and its influence on operating stability of compressor have drawn more attention in recent years, but they are still rare.…”
Section: Introductionmentioning
confidence: 99%